Catalytic Enantioselective 1, 3‐Alkyl Shift in Alkyl Aryl Ethers: Efficient Synthesis of Optically Active 3, 3′‐Diaryloxindoles. Issue 20 (20th April 2018) - Gade, Amol B.; Bagle, Pradip N.; Shinde, Popat S.; Bhardwaj, Vipin; Banerjee, Subhrashis; Chande, Ajit; Patil, Nitin T.
Abstract: Reported is the first organocatalytic asymmetric 1, 3‐alkyl shift in alkyl aryl ethers for the synthesis of chiral 3, 3′‐diaryloxindoles using a chiral Brønsted acid catalyst. Preliminary results showed that each enantiomer of the 3, 3′‐diaryloxindole, and a racemic mixture, showed different antiproliferative activities against HeLa cell lines by using an MTT assay. Abstract : Shifting groups : Reported is the first organocatalytic asymmetric 1, 3‐alkyl shift in alkyl aryl ethers for the synthesis of chiral 3, 3′‐diaryloxindoles using a chiral Brønsted acid catalyst. Each enantiomer of the 3, 3′‐diaryloxindole, and a racemic mixture, showed different antiproliferative activities against HeLa cell lines in an MTT assay.